DYSLEXIC CHILDREN IN PRIMARY EDUCATION AND EFFECTIVE TEACHING METHODOLOGY - S. M. Zokirova (Web of Journals Publishing, 2025)
This article explores the characteristics of dyslexic children in primary education and examines scientifically grounded methods of teaching and support. Dyslexia, being a specific learning difficulty related to language processing, affects reading, writing, and phonological awareness. The article discusses the importance of early diagnosis, individual approach, multisensory techniques, and the use of digital educational technologies. The effective organization of the educational process for dyslexic learners is crucial for their intellectual and social development.
Keywords: Dyslexia, primary education, inclusive education, phonological awareness, multisensory learning, educational support, digital resources.